Projected Real‐World Effectiveness of Using Aggressive Low‐Density Lipoprotein Cholesterol Targets Among Elderly Statin Users Following Acute Coronary Syndromes in Canada - David A. Alter (Wiley, 2018)
BackgroundThe extent to which outcome benefits may be achieved through the implementation of aggressive low‐density lipoprotein (LDL) cholesterol targets in real world settings remains unknown, especially among elderly statin users following acute coronary syndromes. Methods and ResultsA population‐based cohort study consisting of 19 544 post‐acute coronary syndrome statin‐users aged ≥66 years between January 1, 2017 and March 31, 2014 was used to project the number of adverse outcome events (acute myocardial infarction or death from any cause) that could be prevented if all post‐acute coronary syndrome elderly statin users were treated to 1 of 2 LDL cholesterol target levels (≤50 and ≤70 mg/dL). The number of preventable adverse outcomes was estimated by using model‐based expected event probabilities as derived from Cox Proportional hazards models. In total, 61.6% and 25.5% of the elderly patients met LDL cholesterol targets of ≤70 and ≤50 mg/dL, respectively, based on current management. No more than 2.3 adverse events per 1000 elderly statin users (95% confidence interval: −0.7 to 5.4, P=0.62) could be prevented over 8.1 years if all patients were to be treated from current LDL cholesterol levels to either of the 2 LDL cholesterol targets of 70 or 50 mg/dL. ConclusionsThe number of acute myocardial infarctions or death that could be prevented through the implementation of LDL cholesterol targets with statins is negligible among an elderly post‐acute coronary syndrome population. Such findings may have implications for the applicability of newer agents, such as proprotein convertase subtilisin/kexin type‐9‐ inhibitors.